PERILAKU KONSUMSI KOPI SEBAGAI BUDAYA MASYARAKAT KONSUMSI (STUDI FENOMENOLOGI PADA PEMINUM KOPI DI KEDAI KOPI KOTA SEMARANG) - Solikatun, Solikatun; Kartono, Drajat Tri; Demartoto, Argyo (UNIVERSITAS SEBELAS MARET (UNS), 2015)
The change occurring in coffee consuming behavior cannot be apart from the effect of globalization development making the society behaving consumptively. It will result in various changes in the interpretation of coffee consuming behavior in the Semarang society. The objective of research was to find out the coffee consuming behavior, consuming society culture, and tragedy of coffee consuming culture among the coffee drinkers in coffee shops of Semarang City. The theory employed in this study was Jean P Baudrillard’s consuming society theory, Geog Simmel’s modern cultural theory, and Thorstein Veblen’s leisure class theory. This study employed a phenomenological approach, aiming to explore the motive and meaning of action in-depth concerning the coffee consuming behavior as the consuming society culture. The data collection was conducted using direct observation and in-depth interview.The result of research showed that the interpretation of coffee consuming behavior in Semarang society had changed. The coffee consuming behavior the coffee drinkers had could be seen from the actor or coffee drinkers, the activity the do, their appearance, reason of coffee consumption and coffee consumption place. In coffee consuming behavior, not only a cup of coffee was consumed but the coffee drinker also consumed prestige, social status, elegant and exclusive impression, and modern society lifestyle. In this case, what bought and consumed was no more than the signs embedded into consumption objects. The coffee consuming behavior was made to follow the modern society lifestyle emphasizing on prestige, although the coffee drinkers knew that what they consumed sometimes was not as they wanted, for example the taste of coffee beverage served was bitter because it derived from selected coffee seed. The difference of interpretation on coffee consuming behavior between one coffee drinker and another led to coffee drinker typification. The typification of coffee drinkers in interpreting the coffee consuming behavior was divided into two: opened-modern and closed-modern coffee drinker. Keywords: Consumption Behavior, Consuming Society Culture, Cultural Tragedy